Substrate‐Induced Phase of a Benzothiophene Derivative Detected by Mid‐Infrared and Lattice Phonon Raman Spectroscopy. Issue 8 (2nd March 2018) - Schrode, Benedikt; Jones, Andrew O. F.; Resel, Roland; Bedoya, Natalia; Schennach, Robert; Geerts, Yves Henri; Ruzié, Christian; Sferrazza, Michele; Brillante, Aldo; Salzillo, Tommaso; Venuti, Elisabetta
Abstract: The presence of a substrate‐induced polymorph of 2, 7‐dioctyloxy[1]benzothieno[3, 2‐ b ]benzothiophene is probed in microscopic crystals and in thin films. Two experimental techniques are used: lattice phonon Raman and IR spectroscopy. The bulk crystal and substrate‐induced phase have an entirely different molecular packing, and therefore, their Raman spectra are characteristic fingerprints of the respective polymorphs. These spectra can be unambiguously assigned to the individual polymorphs. Drop‐cast and spin‐coated thin films on solid substrates are investigated in the as‐prepared state and after solvent‐vapor annealing. Because Raman spectroscopy is less sensitive with decreasing film thickness, IR spectroscopy is shown to be a more feasible tool for phase detection. The surface‐induced phase is mainly present in the as‐prepared thin films, whereas the bulk phase is present after solvent‐vapor annealing. This result suggests that the surface‐induced phase is a metastable polymorph. Abstract : How does a crystal grow? The appearance of the substrate‐induced phase of a benzothiophene derivative is studied. Samples include thin films prepared by solution processing and single crystals grown from different solvents. The polymorphic structures of the films can be differentiated by means of mid‐IR spectroscopy, whereas lattice phonon Raman spectroscopy is applicable to thicker films and crystals (see figure).